The Impact of Nanochloroquine on Restoration of Hepatic and Splenic Mitochondrial Damage against Rodent Malaria. (16th May 2013) - Tripathy, Satyajit; Das, Sabyasachi; Dash, Sandeep Kumar; Chattopadhyay, Sourav; Roy, Somenath
Abstract : The applications of nanotechnology to pharmacology are the potential appliance of biodegradable polymers and convection-enhanced drug delivery in the diagnostics and treatment of diseases. Chitosan is a natural polysaccharide that has attracted significant scientific interest during the last two decades. The present study was to evaluate the possible effects of chitosan tripolyphosphate conjugated nanochloroquine against Plasmodium berghei infection on select makers of oxidative damage and antioxidant status in mitochondria of liver and spleen. P. berghei infection was developed in Swiss mice by intraperitoneal injection of 200 µL of infected blood. Parasite-infected mice were treated with chloroquine and nanoconjugated chloroquine. Superoxide radical generation, nitrate level, and oxidized glutathione were increased significantly (P < 0.05 ) in the mitochondria of infected group as compared to control group, and reduced glutathione level, activity of SOD, GPx, GR, and GST, and mitochondrial transmembrane potential were decreased significantly (P < 0.05 ), which were increased or decreased significantly (P < 0.05 ) near to normal in nanoconjugated chloroquine treated group than chloroquine treated group. So, the findings may suggest the advantageous role of nanoconjugated chloroquine against the P. berghei induced oxidative damage in hepatic and splenic mitochondria.